Factores psicosociales que influyen en la ansiedad en una madre de familia diagnosticada con covid-19 en la Unidad Educativa Renán Olmedo González en el recinto el Limón del cantón El Empalme - Loor Gaibor, Liz Katherine (2020)
The following case study is from a 31-year-old mother from the Renán Olmedo González Educational Unit, EL Empalme city, using a qualitative approach with the aim of identifying psychosocial factors and their determinants in order to establish the relationship and influence they have with anxiety and in this way propose a solution to the problem. This case study was carried out through the application of techniques such as the interview, medical history, cognitive behavioral techniques such as cost-benefit and relaxation, as well as psychological tests such as the Hamilton anxiety test to measure anxiety and two questionnaires to evaluate social support and reaction to stressful stimuli, guiding diagnosis, which according to CIE-10 and DSM-5 determined that the patient presents F41.1 Generalized Anxiety Disorder. After them, a therapeutic scheme was proposed in order to reduce anxiety levels in the patient.